Pulmonary rehabilitation integrated coached exercise training for patients with COPD: a study protocol for a randomized controlled trial - Yuting Jing; Yuying Ma; Hongxing Zhang; Zhenhu Wu; Yongwen Li; Haoxuan Li; Minling Huang; Lin Lin; Yinji Xu (Trials, 2023)
Abstract Background Chronic obstructive pulmonary disease (COPD) is the most common chronic lung disease creating an immense burden on social health care systems. Pulmonary rehabilitation (PR) has proven to be effective in patients with COPD. However, exercise training as the basis of PR becomes extremely tedious, occasionally causing a loss of perseverance in patients. Therefore, we considered an approach that makes this technique interesting and easier to persist. The aim of this project was to explore an exercise training approach based on PR-integrated coached exercise training to promote the new exercise training approach as a form of group rehabilitation activity in the future. Methods Participants will be randomly divided into the trial and control groups. The trial group will be treated with PR-integrated coached exercise training (plus usual care). All exercise programs will be guided by sports coaches with a physical education background. Meanwhile, the control group will receive traditional PR and home exercises, including walking and swimming. The study will last for 12 weeks. The primary outcome measure is exercise tolerance using the 6-min walking test and secondary outcomes are the peak oxygen uptake of cardiopulmonary exercise tests, the COPD Assessment Test, and the St. Georges Respiratory Questionnaire. Other evaluated outcomes include changes in postbronchodilator forced expiratory volume at 1st second, forced vital capacity, body fat and muscle composition, and mental status measured using the Hamilton Anxiety and Depression Scales. Discussion This study provides a simple, feasible, repeatable, and fun exercise training approach. To the best of our knowledge, there are no randomized controlled trials in the existing literature on PR-integrated coached exercise. The protocol shared in our study can be used as a reference for exercise training in patients with COPD. Trial registration Ethical approval (BF2020-236–02) was obtained from the Guangdong Provincial Hospital of Chinese Medicine Human Research Ethics Committee. All participants signed an informed consent form. ChiCTR-2100043543. The registration date is 2021/02/21 and it is the third version.